Cost Implications of Reactive Versus Prospective Testing for Dihydropyrimidine Dehydrogenase Deficiency in Patients With Colorectal Cancer: A Single-Institution Experience. Issue 4 (29th September 2018) - Murphy, Con; Byrne, Stephen; Ahmed, Gul; Kenny, Andrew; Gallagher, James; Harvey, Harry; O'Farrell, Eoin; Bird, Brian
Background: Severe toxicity is experienced by a substantial minority of patients receiving fluoropyrimidine-based chemotherapy, with approximately 20% of these severe toxicities attributable to polymorphisms in the DPYD gene. The DPYD codes for the enzyme dihydropyrimidine dehydrogenase (DPD) important in the metabolism of fluoropyrimidine-based chemotherapy. We questioned whether prospective DPYD mutation analysis in all patients commencing such therapy would prove more cost-effective than reactive testing of patients experiencing severe toxicity. Methods: All patients experiencing severe toxicity from fluoropyrimidine-based chemotherapy for colorectal cancer in an Irish private hospital over a 3-year period were tested for 4 DPYD polymorphisms previously associated with toxicity. The costs associated with an index admission for toxicity in DPD-deficient patients were examined. A cost analysis was undertaken comparing the anticipated cost of implementing screening for DPYD mutations versus current usual care. One-way sensitivity analysis was conducted on known input variables. An alternative scenario analysis from the perspective of the Irish health-care payer (responsible for public hospitals) was also performed. Results: Of 134 patients commencing first-line fluoropyrimidine chemotherapy over 3 years, 30 (23%) patients developed grade 3/4 toxicity. Of these, 17% revealed heterozygote DPYD mutations. The cost of hospitalization for the DPYD -mutated patients was €232 061, while prospectively testing all 134 patients would have cost €23 718. Prospective testing would result in cost savings across all scenarios. Conclusions: The cost of hospital admission for severe chemotherapy-related toxicity is significantly higher than the cost of prospective DPYD testing of each patient commencing fluoropyrimidine chemotherapy.